Management Options for Improving Flowering in Citrus Production - Leigh Archer; Miurel Brewer; Bikash Adhikari; Eduardo Esteves; Christopher Vincent; Tripti Vashisth (EDIS)
The final fruit yield and, ultimately, returns a grower receives from any given harvest is directly related to the number of viable flowers that are generated and the proportion of those flowers that produce fruit. A grower can improve the ability for their trees to consistently produce a profitable crop of fruit by understanding the steps involved in flowering and controlling the transition to reproductive growth. This new 6-page publication of the UF/IFAS Horticultural Sciences Department was written by Leigh Archer, Miurel Brewer, Bikash Adhikari, Eduardo Esteves, Christopher Vincent, and Tripti Vashisth. https://edis.ifas.ufl.edu/hs1399